Hey use photo math is gonna help you a lot
I don't think this is middle school...
(2^8 x 3^-5 x 6^0)^-2 x ((3^-2)/(2^3))^4 x (2^28)
(256 x (1/243))^-2 x ((1/9)/(8))^4 x 268435456
1.05349794239^-2 x (<span>0.01388888888)^4 x 268435456
</span><span>
0.90101623534 x </span><span>3.72108862e-8 x 268435456
</span>8.99999997623
9
9 is your answer.
Multiply both sides by x - 3 to get :
y(x - 3) = 2
yx - 3y = 2
yx = 2 + 3y
x = (2 + 3y)/y
Hope this helps! Any questions let me know :)
Answer:
The correct answer would be the bottom equation.
Step-by-step explanation:
y=7.25x
y=7.25(3)
y=21.75
y=7.25(4)
y=29.00
y=7.25(5)
y=36.25